Visceral obesity, muscle mass and outcome in rectal cancer surgery after neo-adjuvant chemo-radiation. (May 2016) - Heus, Colin; Cakir, Hamit; Lak, Arjan; Doodeman, Hiëronymus J.; Houdijk, Alexander P.J.
Abstract: Background: Preoperative chemoradiation has become a routine modality in the treatment of rectal carcinoma that may impair a patients general condition. In these patients, it is important to identify factors that influence postoperative recovery. Visceral obesity(VO) as a metabolic risk factor was studied in rectal cancer patients receiving preoperative chemoradiation. Aim: The impact of VO on post-operative outcome in rectal carcinoma surgery after preoperative chemoradiation was studied. In addition, the effect of chemoradiation on body composition was studied. Method: The visceral fat area(VFA), total fat area(TFA) and skeletal muscle area(SMA) were measured on cross-sectional CT-slides in 74 patients who underwent rectal cancer surgery after chemoradiation. CT-scans taken before and after chemoradiation were analysed. Associations between VFA, per- and postoperative complications were studied. A VFA of 100 cm 2 and 130 cm 2 was used to differentiate between non-VO and VO. Results: Using a VO cut-off point of a VFA of 100 cm 2, the VO patients had more per-operative blood loss(471 mL vs 271 mL p = 0.020), a higher complication rate(10% vs 49% p = 0.001), more ileus(2% vs 28% p = 0.027) and a longer length of stay(9.7days vs 13days p = 0.027). When a VFA of 130 cm 2 was used, VO patients showed more complications(17% vs 55%, p = 0.001) and ileus(10% vs 32% p = 0.017). During chemoradiation the SMA increased(Mean difference: 2.2 cm 2 p = 0.024), while the VFA showed no change. Conclusion: It appears that VO is associated with co-morbidity and poor outcome in rectal cancer patients. Using different cutoff values for VO different associations with outcome were found. SMA increased during chemoradiation, a phenomenon that remains to be explained. Highlights: Visceral obesity is associated with co-morbidity and poor outcome in rectal cancer surgery. Visceral obesity is associated with more complications and a longer length of stay in rectal cancer surgery. Different cut-off values for visceral obesity different associations with outcome were found. Skeletal muscle area increased during chemoradiation, a phenomenon that remains to be explained.